2013
DOI: 10.1161/atvbaha.112.301099
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Talk of Receptor Activator of Nuclear Factor-κB Ligand Signaling With Renin–Angiotensin System in Vascular Calcification

Abstract: V ascular calcification is highly correlated with cardiovascular mortality and associated with hypertension.1 Intima arterial calcification occurs in conjunction with atherosclerosis, and media calcification is usually present with systemic mineral imbalance caused by chronic renal disease. Although both types are pathologically distinct, there is an association between the molecular mechanism regulating vascular calcification in intima and media. We and others have described the involvement of receptor activa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(34 citation statements)
references
References 32 publications
2
32
0
Order By: Relevance
“…Previous reports showed an inconsistent expression level of RANK and RANKL in OPG −/− mice compared with WT mice: increased mRNA levels of RANK and RANKL in the aorta (21); the same expression level of RANKL mRNA expression in osteoblasts (26,27); and a decreased expression level of RANK mRNA in osteoclasts in 12-wk-old mice followed by an increased level at 20 and 28 wk (28). From this viewpoint, the expression level of RANK and RANKL in OPG −/− might be dependent in cells or tissue.…”
Section: Discussionmentioning
confidence: 85%
“…Previous reports showed an inconsistent expression level of RANK and RANKL in OPG −/− mice compared with WT mice: increased mRNA levels of RANK and RANKL in the aorta (21); the same expression level of RANKL mRNA expression in osteoblasts (26,27); and a decreased expression level of RANK mRNA in osteoclasts in 12-wk-old mice followed by an increased level at 20 and 28 wk (28). From this viewpoint, the expression level of RANK and RANKL in OPG −/− might be dependent in cells or tissue.…”
Section: Discussionmentioning
confidence: 85%
“…There is evidence that NFkB signaling pathway is required to trigger and propagate osteogenic program and vascular calcification [24][25][26]. Further studies point to involvement of the NFkB transcriptional activity and the Erk (Extracellularsignal Regulated Kinase) pathway for C5aR-related functional responses [2,27].…”
Section: Upar-c5ar Axis Activates Erk and Nfjb Upon Msc Osteogenic DImentioning
confidence: 97%
“…Osteoblasts express OPG and RANKL, which regulate osteoclast differentiation through the activation of RANK [40]. The present study showed that exenatide could decrease the expression of RANKL and inhibit the expression of ALP, OC, and Runx2 in human CVSMCs.…”
Section: Discussionmentioning
confidence: 60%